Information Accounting System on Small and Medium Enterprises: Bibliometric Analysis - Nugraha, Ginanjar Adi; Firmansyah, Irman; Dinanti, Aldila (Journal of Applied Accounting and Taxation, 2025)
This research aims to investigate publication trends on the topic of accounting information systems in SMEs. This is intended to fill the research gap regarding the absence of previous research that discusses the development of publications on this topic. The method used is bibliometric analysis with the Scopus database in the publication range from 2014 to 2023. The search keywords use Bolean, namely "account* information system*" OR "information system*" AND "SMEs" OR "small and medium enterprise*", so that we get 982 publications. The research results found that the most productive publication sources were the Iberian Conference On Information Systems And Technologies Cisti and Advances In Intelligent Systems And Computing, while the publication that had the highest impact was Procedia Computer Science. The most prolific writers were Kamariotou and Kitsios. Both of them are also writers with the highest impact. Bina Nusantara University was identified as the most productive institution, and Indonesia was the most productive country, but the one most cited was France. This information can be an important basis for researchers, practitioners and policy makers in understanding the latest dynamics and developments in this field.